2011
DOI: 10.1111/j.1365-2036.2010.04559.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined lung‐sound and reflux‐monitoring: a pilot study of a novel approach to detect nocturnal respiratory symptoms in gastro‐oesophageal reflux disease

Abstract: SK and VG contributed equally and should both be considered first authors. 2UK and VE contributed equally and should both be considered last authors. SUMMARY BackgroundIncreased prevalence of respiratory symptoms has been commonly reported in patients with gastro-oesophageal reflux disease (GERD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
7
0
5
Order By: Relevance
“…As might be expected, studies using ambulatory acoustic systems to record cough sounds [38,39] have reported greater prevalence for both reflux-cough and cough-reflux associations than other techniques, such as manometry [20,21,40]. This is probably because it easier to identify single coughs using acoustic systems than manometry, where a single rapid pressure changes could represent either cough or artefact, such as clearing of the throat, and thus be rejected on a cautionary level by the observer.…”
Section: Introductionmentioning
confidence: 72%
“…As might be expected, studies using ambulatory acoustic systems to record cough sounds [38,39] have reported greater prevalence for both reflux-cough and cough-reflux associations than other techniques, such as manometry [20,21,40]. This is probably because it easier to identify single coughs using acoustic systems than manometry, where a single rapid pressure changes could represent either cough or artefact, such as clearing of the throat, and thus be rejected on a cautionary level by the observer.…”
Section: Introductionmentioning
confidence: 72%
“…However when the precise timing of cough and reflux events has been interrogated, up to 48% of patients with chronic cough display significant temporal associations (positive symptom association probability), with reflux events preceding cough more frequently than would be expected by chance alone [2731]. These associations have been described for reflux events in the distal esophagus and therefore support the notion that a neuronal mechanism might explain the link between reflux and cough events.…”
Section: Jaclyn a Smith Against The Motionmentioning
confidence: 81%
“…Together with use of the SAP, these technologies greatly improve the objectivity of the analysis. All recent studies utilizing one or another variation of these enhancements have consistently demonstrated that in a substantial proportion of chronic cough patients (20–48%) cough follows reflux more frequently than expected by chance [2731]. Furthermore, the pH of the reflux events preceding cough does not matter; reflux events of pH> 4 are equally important as those with pH italic>4 [3031].…”
Section: Peter J Kahrilas For the Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Various studies have supported this documentation and shown a relationship between these two disorders. (2,3) Chronic cough significantly affects the quality of life of these patients. (4) Case Report A 65 years old male presented with chronic cough, sputum and respiratory difficulty with repeated attacks of respiratory distress since 18 months having strong relationship with sleep and heavy meals.…”
Section: Introductionmentioning
confidence: 99%